Archaeologies of Climate Change: Perceptions and Prospects - Britton, Kate; Hillerdal, Charlotta (Études Inuit Studies, 2019)
Climate change is the biggest challenge facing humanity today, and discussions of its effects—from habitat loss to psychological impacts—can be found in most academic disciplines. Among the many casualties of contemporary climatic change is the archaeological heritage of Arctic and subarctic regions, as warming, erratic weather patterns, coastal erosion, and melting permafrost threaten the anthropogenic and ecological records found in northern environments. Archaeology is uniquely positioned to provide long-term perspectives on human responses to climatic shifts, and to inform on the current debate. In addition, the practice of archaeological research and assimilation of archaeological heritage into contemporary society can also address or even mitigate some of the sociocultural impacts of climate change. Focusing on the Yup’ik communities and critically endangered archaeology of the Yukon–Kuskokwim (Y–K) Delta, Alaska, here we argue community archaeology can provide new contexts for encountering and documenting the past, and through this, reinforce cultural engagement and shared cultural resilience. We emphasize the benefits of archaeological heritage and the practice of archaeology in mitigating some of the social and psychological impacts of global climate change for communities as well as individuals. We also propose that archaeology can have a role in reducing psychological distance of climate change, an acknowledged barrier that limits climate change action, mitigation, and adaptation, particularly in regions where the impacts of contemporary climate change have not yet been immediately felt.